Mediating Role of Intimate Partner Violence Between Emotional Dependence and Addictive Behaviours in Adolescents - Macía, Patricia; Estevez, Ana; Iruarrizaga, Iciar; Olave, Leticia; Chávez, Mᵃ Dolores; Momeñe, Janire (Frontiers in Psychology, 2022)
Objective: Intimate partner violence (IPV) has been related to emotional dependence and addictive disorders. This study aims to provide a global approach to analyze the relationship between these variables and to determine the factors underlying permanence in violent relationships. Methods: It is a non-experimental, cross-sectional correlational design study. Participants had to have at least one dating relationship for at least one month to complete the questionnaire, which included the following instruments: emotional dependence scale (DEN), scale of violence in dating relationships (VREP) and impulse control disorders scale (MULTICAGE CAD 4). Results: The sample consisted of 1.533 adolescents, 53.9% were male (n = 826) and 46.1% female (n = 707), between 14 and 18 years. Emotional dependence correlated significantly with received violence (r=.37, p<.001). Compulsive spending is strongly associated with emotional dependence (r=.21, p<.001), whereas sex addiction is associated with received violence to a greater extent (r=.18, p<.001). Received violence mediates on emotional dependence and addictions. Conclusions: IPV is a risk factor for the perpetuation ofaddictive behaviours. It is advisable to promote affective education for developing resilience and adequate coping.